![x^2 - 4x - 9 = 29 \\ x^2 - 4x - 9 - 29 = 0 \\ x^2 - 4x - 38 = 0 \\ x= \frac{-b \pm \sqrt{ b^{2} -4ac} }{2a} ](https://tex.z-dn.net/?f=x%5E2%20-%204x%20-%209%20%3D%2029%20%5C%5C%20x%5E2%20-%204x%20-%209%20-%2029%20%3D%200%20%5C%5C%20x%5E2%20-%204x%20-%2038%20%3D%200%20%5C%5C%20x%3D%20%5Cfrac%7B-b%20%5Cpm%20%20%5Csqrt%7B%20b%5E%7B2%7D%20-4ac%7D%20%7D%7B2a%7D%20%0A)
; where a = 1, b = -4 and c = -38
Answer:
38°
Step-by-step explanation:
The angle 1 is 63°
The angle 2 is the same of angle 1
so :
63°+79°=142°
then :
180° - 142° = 38°.
The answer is 50 y squared minus 4 x squared
Answer:
1/6 or one sixth
Step-by-step explanation: